Produção de ácido 3-indolacético, potencial rizogênico e indução de respostas de defesa por Streptomyces SP. em plantas de eucalipto para o controle de botrytis cinerea - Salla, Tamiris Daros (2014)
Eucalyptus is an economically important woody species, especially as a raw material in many industrial sectors. Brazil ranks the second worldwide position in acreage, totalizing approximately three million hectares. Eucalyptus species are very susceptible to pathogens such as Botrytis cinerea (gray mold), which leads to mortality of cuttings in rooting phase. Biological control of plant diseases using soil microorganisms has been considered an alternative to reduce the use of pesticides and pathogen attack. Plant growth promoting rhizobacteria can act directly on plant development for production of phytohormones or indirectly as antagonists to pathogens, as well as promote changes in secondary metabolism, and hence inducing of systemic resistance. In this study, the direct roleof Streptomyces isolates in plant development was evaluated through the production of auxin and rhizogenic potential in Eucalyptus grandis and E. globulus plants, as well as indirectly, by modulation of the secondary metabolism, and induction of sistemic resistence in plantselicited with Streptomyces sp. and challenged with the pathogenic fungus B. cinerea. Metabolic responses were evaluated throughactivity of plant defense enzymes (PPO and POX) and induced secondary compounds (total phenolics and quercetinic-flavonoids fraction). The incidence and progression of gray mold disease on plants elicited Streptomyces sp. PM9, and coculture of these microorganisms (Streptomyces and B. cinerea) were also evaluated. Streptomyces sp. PM5 and PM9 isolates produced more auxin than the other isolates tested. Streptomyces sp. PM9 showed the highest rhizogenic potential on Eucalyptus sp. and modulated secondary metabolism of these plants. Antagonism of this isolated over B. cinerea was evidenced. Plants elicited with Streptomyces sp. PM9 and challenged with B. cinerea showed changes in PPO and POX enzymes and levels of phenolic compounds at different time points of analysis, which may be related to initial defense response. Phenolic compounds chlorogenic acid and gallic acid were, on average, the most abundant, while caffeic acid, benzoic acidand catechin were induced at specific time points. A delay in the onset of disease was significant in plants of E. grandis elicited with Streptomyces. The induction of resistance, disease delay and antagonism against B. cinereaindicate the capacity of Streptomyces sp. PM9 as an inducer of plant systemic resistance, and poses this microorganism as a potential candidate for biological control programs in nurseries of Eucalyptus. Interaction of rhizobacteria with eucalyptus plant, as well as the modulation of defense mechanisms may contribute to the establishment of new biocontrol strategies applied to forestry.